An Analysis Of Illocutionary Act By The Main Character In The Turning Red Movie - Futri Rahayu; Galuh Dwi Ajeng; Aksendro Maximilian (JETA (Journal of English Teaching and Applied Linguistic), 2026)
This research aims to analyze the illocutionary acts performed by the main character, Meilin "Mei" Lee, in the animated film "Turning Red" (2022). The study focuses on identifying the types of illocutionary acts utilized by Mei throughout the film, reflecting her emotional journey and character development. Employing a qualitative method with a content analysis approach, data were collected from key dialogues featuring Mei, resulting in a total of 71 analyzed utterances. The findings reveal that Mei's speech acts can be categorized into four types: directives (16 instances), expressives (21 instances), representatives (18 instances), commisives (6 instances) and declaratives (10 instances). This analysis highlights how Mei's use of language not only conveys her internal struggles and relationships but also underscores the broader themes of identity and self-acceptance in the film.